Economic Transformation: Navigating Challenges And Embracing Opportunities In Islamic Economics And Finance Across Southeast Asia - Dayu, Wulan; Harahap, Isnaini; M. Nawawi, Zuhrinal (Publisher Cv. Inara, 2024)
The research aims to comprehensively understand challenges impeding the growth of Islamic economic systems in Southeast Asia and explore opportunities for sustainable development. It contextualizes the economic transformation in the region, emphasizing the unique role of Islamic economics and finance. Challenges like regulatory complexities, market uncertainties, and global economic shifts are analyzed, providing insights into impediments faced by the Islamic finance sector. The article explores strategies employed by Southeast Asian countries to promote Islamic economics and finance, assessing policy effectiveness and collaborative efforts. It highlights the role of financial inclusion, education, and technology in overcoming hurdles. On a positive note, the study identifies growth opportunities in regional cooperation, innovative financial instruments, and Islamic finance's potential contribution to sustainable development goals. Emphasizing the importance of embracing these opportunities, the research contributes to the discourse on economic transformation in Southeast Asia. The findings aim to inform policymakers, financial institutions, and scholars, fostering understanding for a more inclusive, sustainable, and prosperous economic future in the region.